THE ULIANOV CHUVASH STATE UNIVERSITY: BASING ON TRADITIONS TO INNOVATIONS - Andrey Yu. Aleksandrov; Vladimir V. Afanasiev (Высшее образование в России)
The article presents the historical path, the current state and the development prospects of the largest university in the Chuvash Republic - The Ulianov Chuvash State University. The authors examine various types of activities of the university: education, scientific research, training, and others.